2022
DOI: 10.1108/ijhma-04-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive impacts of lifestyles on preference for interior public space of high-rise building apartment

Abstract: Purpose While interior public space can be one of the most important criteria in designing high-rise residential buildings in urban environments in practitioners’ opinion, this study aims at investigating the importance of this criterion from consumers’ lifestyle standpoint. In particular, this study aims to examine the effects of different lifestyle orientations on consumers’ preference for this housing feature. Three relevant lifestyles are investigated including independence, family-orientation and homebody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
2
0
0
Order By: Relevance
“…A security guard in the housing area will check on unknown people or visitors before letting them into the Condominium or apartment. Our finding thus corroborates with the findings of Nguyen et al (2022) about the lifestyle orientation that prioritises other social qualities, such as safety from crime or the social status of residents when choosing a house. That gives the residents a feeling of security and comfort.…”
Section: Findings and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A security guard in the housing area will check on unknown people or visitors before letting them into the Condominium or apartment. Our finding thus corroborates with the findings of Nguyen et al (2022) about the lifestyle orientation that prioritises other social qualities, such as safety from crime or the social status of residents when choosing a house. That gives the residents a feeling of security and comfort.…”
Section: Findings and Discussionsupporting
confidence: 89%
“…Besides, this research also supported the study by Kam et al (2018) claimed that the house's location is more significant than the house itself. Furthermore, this study also supported past research by Nguyen, et al (2022) and Yaacob et al (2018) which the researchers indicated that distance has a positive relationship with housing purchasing. Finally, this study has supported the research by Hartono et al (2022) that emphasises the travel time to the workplace, medical amenities, and educational institutions are the critical factors in choosing the house.…”
Section: Findings and Discussionsupporting
confidence: 88%